Genomic insights into Dactylosporangium sp. AC04546, a rubber degrader with three latex clearing proteins - Basik, Ann Anni; Gibu, Namiko; Kawagiwa, Yukimura; Ng, Siuk-Mun; Yeo, Tiong Chia; Sudesh, Kumar; Kasai, Daisuke (Frontiers in Microbiology, 2024)
With more than 100 rubber degrading strains being reported, only 9 Lcp proteins isolated from Nocardia, Gordonia, Streptomyces, Rhodococcus, Actinoplanes and Solimonas have been purified and biochemically characterized. A new strain Dactylosporangium sp. AC04546 (strain JCM34239) isolated from soil sample collected in Sarawak Forest was able to grow and utilize natural or synthetic rubber as the sole carbon source. Strain AC04546 has a large circular genome of 13.08 Mb with a G+C content of 72.1%. The genome contains 11,865 protein coding sequences with 3 latex clearing protein (lcp) genes located on its chromosome. The genetic organization of the lcp gene cluster is similar to two other reported rubber degrading strains, Actinoplanes sp. OR16 and Streptomyces sp. CFMR 7. All 3 Lcp from strain AC04546 were expressed in Escherichia coli and exhibited degrading activity against natural rubber. The distinctiveness of strain AC04546 with other characterized rubber degrading strains is being reported here.